2020
DOI: 10.1002/cbic.201900776
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Diol Dehydration by a Promiscuous Radical‐SAM Enzyme Homologue of the Antiviral Enzyme Viperin (RSAD2)

Abstract: has made ap rovisionalp atent application based on the discoveries demonstrated in this manuscript.Keywords: antiviral agents · nucleotide analogues · radical-SAM enzyme · tyrosyl radicals · viperin Figure 6. The proposed mechanism of catalysis by TtRSAD2. The 5'-dAdo radicalabstractst he Ha tom (red) at the C4' position of ribose to generate a C4'-centred radical intermediate. As ar esult of hyperconjugation between a po rbitalonC 4' and the s C3'ÀO3' orbital, assisted by ap rotein amino acid residue( AH), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 62 publications
1
40
1
Order By: Relevance
“…First, we measured whether a mixture of ddhCTP and 5′‐dA produced by the enzymatic activity of RSAD2 can inhibit the activity of GAPDH. To this end, we produced the mixture of ddhCTP and 5′‐dA using RSAD2 [21] (Methods). Then, the NAD + ‐dependent conversion of G3P to 1,3BPG by GAPDH was measured either directly or alternatively, using an enzyme‐coupled assay (Methods).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…First, we measured whether a mixture of ddhCTP and 5′‐dA produced by the enzymatic activity of RSAD2 can inhibit the activity of GAPDH. To this end, we produced the mixture of ddhCTP and 5′‐dA using RSAD2 [21] (Methods). Then, the NAD + ‐dependent conversion of G3P to 1,3BPG by GAPDH was measured either directly or alternatively, using an enzyme‐coupled assay (Methods).…”
Section: Resultsmentioning
confidence: 99%
“…We have confirmed that the thermostable fungal RSAD2 from Thielavia terrestris (TtRSAD2) can efficiently catalyse transformation of CTP to ddhCTP [21]. Thus, to prepare a mixture of ddhCTP and 5′‐dA we used TtRSAD2.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations